Pelaksanaan Praperadilan di Pengadilan Negeri Banda Aceh - Mahfud Mahfud (Universitas Syiah Kuala, 2012)
ABSTRACT: Article 1 point 10 of the Indonesian Crininal Procedure states that the First Instance Court has an authority to check and decide regardong the validity of the arrest, detention, investigation stop and prosecution stop and remedy or rehabilitation for some one which the case stopped in the level of investigation and prosecution. However, in the hjurisdiction of the court the process of pretrials are dismissed by the court. This research aims at identifying the process and the reason for bringging it by the defendants. The Applying of Prejustice Process at the First Instance Court of Banda Aceh